2018
DOI: 10.4034/pboci.2018.181.49
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Patient Satisfaction on Quality of Public Dental Health Service from Different Dimensions in Indonesia

Abstract: Objective: To verify user satisfaction with oral public health services in different treatment dimensions and relate them to demographic conditions. Material and Methods: This study using pilot pathfinder design, conducted in Bantaeng Regency in January 2018. The sample consisted of 114 participants. Data were collected using structured questionnaires, which have been designed according to this survey which has eighteen questions corresponding to the object, with response patterns: satisfied, more or less and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 12 publications
1
8
1
7
Order By: Relevance
“…Women pay more attention to their appearance, while men do not heed it. In addition women are more sensitive to emotion and empathy while men are more likely to care about better physical environment and quicker and more flexible response than women [12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Women pay more attention to their appearance, while men do not heed it. In addition women are more sensitive to emotion and empathy while men are more likely to care about better physical environment and quicker and more flexible response than women [12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it should be pointed out that, in addition to its verifiable dimension quality, it is the first factor by which users can perceive the materialization of the service received. However, for Samad, Akbar, Pasiga, Pratiwi, Anwar, Djamaluddin and Afiyah (2018) in their study it is concluded that tangibility is the dimension with the highest level of satisfaction having a positive correlation between tangibility and quality of care and on the other hand the dimension of dental health care shows the lowest satisfaction.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, another research showed that women visit more providers of dental and oral health services because more attention to the aesthetic and clean teeth and mouth. Women pay more attention to their appearance, while men do not heed it other than that women are more sensitive to emotion and empathy while men are more likely to care about better physical environment and faster and more flexible responses than women [17][18][19][20].…”
Section: Resultsmentioning
confidence: 99%